1973
DOI: 10.1073/pnas.70.8.2340
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Allantoin Degradative Enzymes in Saccharomyces cerevisiae by the Last Intermediate of the Pathway

Abstract: Saccharomyces cerevisiae can degrade allantoin in five steps to glyoxylate, ammonia, and "CO2."We previously demonstrated that synthesis of the urea carboxylase-allophanate hydrolase multienzyme complex is contingent upon the presence of allophanic acid, the product of the urea carboxylase reaction. Since these enzymes catalyze the last two reactions of allantoin degradation, experiments were performed to establish whether or not the presence of allophanic acid was required for synthesis of any other enzymes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 9 publications
2
46
0
Order By: Relevance
“…For DNA fiber autoradiography, cells were grown in medium containing 5 pg/ml uridine (23), pulse labeled with low specific activity [5, Ci/mM, 100 ttCi/ml ; Amersham Corp ., Arlington Heights, Ill.), washed quickly by filtration, and incubated in the same medium with fivefold higher specific activity [5,6-'Hjuracil (44.5 Ci/mM, 100 pCi/ml).…”
Section: Strains Media and Radiolabelingmentioning
confidence: 99%
“…For DNA fiber autoradiography, cells were grown in medium containing 5 pg/ml uridine (23), pulse labeled with low specific activity [5, Ci/mM, 100 ttCi/ml ; Amersham Corp ., Arlington Heights, Ill.), washed quickly by filtration, and incubated in the same medium with fivefold higher specific activity [5,6-'Hjuracil (44.5 Ci/mM, 100 pCi/ml).…”
Section: Strains Media and Radiolabelingmentioning
confidence: 99%
“…Genes encoding the allantoin-degradative system in Saccharomyces cerevisiae, for example, respond to both induction and nitrogen catabolite repression (15,25,38). The five enzyme activities of this system are present at relatively low basal levels unless compounds that can be degraded to allophanate are added to the culture medium (15). In the presence of this native inducer or its gratuitous analog oxalurate the levels of these enzymes dramatically increase (33).…”
mentioning
confidence: 99%
“…Nitrogen catabolic systems are particularly useful for such investigations, because most are subject to multiple layers of regulation. Genes encoding the allantoin-degradative system in Saccharomyces cerevisiae, for example, respond to both induction and nitrogen catabolite repression (15,25,38). The five enzyme activities of this system are present at relatively low basal levels unless compounds that can be degraded to allophanate are added to the culture medium (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The four degradative enzymes and at least one of the associated transport systems are inducible. Allophanate, the last pathway intermediate, and oxalurate (OXLU) function as native and gratuitous inducers, respectively (5,19). Hybridization experiments have demonstrated that, upon induction, increases in several pathway' enzymes correlate with similar increases in steadystate levels of mRNA (see Fig.…”
mentioning
confidence: 99%